2008
DOI: 10.1111/j.1464-5491.2008.02542.x
|View full text |Cite
|
Sign up to set email alerts
|

Peer advisers compared with specialist health professionals in delivering a training programme on self‐management to people with diabetes: a randomized controlled trial

Abstract: Aims To assess the effectiveness and acceptability of peer advisers in diabetes in delivering a programme of training on self-management for people with diabetes.Methods Adults with diabetes were randomly allocated to an education programme delivered either by trained peer advisers or by specialist health professionals. The primary outcome measure was change in knowledge tested before and at the conclusion of the four courses, each consisting of six sessions. Glycated haemoglobin and Diabetes Care Profile were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
90
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(96 citation statements)
references
References 15 publications
4
90
1
1
Order By: Relevance
“…[3][4][5][6][7][8][9][10][11][12][13][14][33][34][35][36] The 12 interventions included seven RCTs, four studies using a pre-/postdesign, 6,8,10,13 and one study using nonrandomized allocation of intervention and comparison groups. 14 Intervention delivery Face-to-face, group-based programs.…”
Section: Studies Includedmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6][7][8][9][10][11][12][13][14][33][34][35][36] The 12 interventions included seven RCTs, four studies using a pre-/postdesign, 6,8,10,13 and one study using nonrandomized allocation of intervention and comparison groups. 14 Intervention delivery Face-to-face, group-based programs.…”
Section: Studies Includedmentioning
confidence: 99%
“…During the past decade, there has been a proliferation of research examining the feasibility, acceptability, and health-related impact of peer support interventions in the context of diabetes care. [3][4][5][6][7][8][9][10][11][12][13][14] Based on a review of peer support interventions for patients with diabetes, Heisler 15,16 identified five models of peer support, including 1) face-to-face group self-management programs, 2) peer coaches or mentors, 3) community health workers (CHWs), 4) telephone-based peer support, and 5) Internet or e-mail-based peer support.…”
mentioning
confidence: 97%
“…21,22 There is strong evidence that motivational interviewing can facilitate lifestyle change. [23][24][25] It appears from this study that there is a need for increased provision of such services because a few minutes with a GP or practice nurse a few times a year is insufficient to address the habitual behaviours that contribute to the condition.…”
Section: Discussionmentioning
confidence: 99%
“…peer advisors in the Isle of Wight). 8 The questions that come to the fore are: 'Does peer support make a difference to the person, to their diabetes and to health services?' and 'Is there a potential for peer support to help us deal with the diabetes epidemic?'…”
Section: Different Forms Of Peer Supportmentioning
confidence: 99%